Price limits are not always bad : a thesis presented in partial fulfilment of the requirements for the degree of Masters of Business Studies in Finance at Massey University, Albany, New Zealand, December 2006 - Ding, Haina (Massey University, 2006)
Regulators impose price limits on daily price movements to protect investors from excessive volatility, but several empirical studies have cast serious doubt on the benefits of such mechanisms. Using a large cross-sectional sample combined with intraday data from the Tokyo Stock Exchange, this study finds evidence that partially supports conventional criticisms that price limits spread out volatility, delay price discovery, and interrupt trading activities. More importantly, the transaction data analysis reveals that price limits help to reduce order imbalance and improve information asymmetry, justifying the existence of price limits on the Tokyo Stock Exchange. JEL Classification: G10; G14 Keywords: Price limit; Order imbalance; Information asymmetry; Tokyo Stock Exchange.
Keywords: Japan; Stock exchanges; Tōkyō Shōken Torihikijo